2018
DOI: 10.22454/fammed.2018.853841
|View full text |Cite
|
Sign up to set email alerts
|

fmCASES National Examination as a Pretest in a Family Medicine Clerkship

Abstract: Background and Objectives: Pretests have been shown to contribute to improved performance on standardized tests by serving to facilitate development of individualized study plans. fmCASES is an existing validated examination used widely in family medicine clerkships throughout the country. Our study aimed to determine if implementation of the fmCASES National Examination as a pretest decreased overall failure rates on the end-of-clerkship National Board of Medical Examiners (NBME) subject examination, and to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Additionally, we can explore approaches for integrating VPCs and SAQs in an active learning environment. Recent studies have begun to examine the use of validated examinations as pretests for NBME subject examinations [ 24 ]. This exploration could contribute to developing additional SAQs with the necessary psychometric properties to support students’ desire for study aids that will positively affect examination performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we can explore approaches for integrating VPCs and SAQs in an active learning environment. Recent studies have begun to examine the use of validated examinations as pretests for NBME subject examinations [ 24 ]. This exploration could contribute to developing additional SAQs with the necessary psychometric properties to support students’ desire for study aids that will positively affect examination performance.…”
Section: Discussionmentioning
confidence: 99%
“…Moroz et al [ 23 ] showed that increases in scores on the self-assessment examinations in physical medicine and rehabilitation were significantly related to improvements in board scores. Nguyen et al [ 24 ] report that students who took a comprehensive family medicine exam at the beginning of the clerkship and received educational support based on the exam results significantly reduced their NBME subject exam failure rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 fmCASES National Examination is a helpful formative assessment tool for students beginning their family medicine clerkship. 7 However, use of MedU (now Aquifer) virtual cases did not impact NBME scores. 8 Performance on CSMS self-assessments and clinical science subject examinations was related.…”
mentioning
confidence: 98%